PENGARUH SISTEM POLITIK MASYARAKAT JAWA TERHADAP SISTEM POLITIK DI INDONESIA - Agung Ariyanto; Dio Dera Darmawan; Ganang Setiyo Nugroho (Universitas Sebelas Maret, 2013)
In the midst of the multicultural reality of Indonesia, the existence of the Javanesse community can be quite exist in Indonesian society. This can be seen in the fact that most of the population is Javanese society, and in their development in the sense of having spread wander down to the outposts the country, until it can be said that the Java community has ebar ters throughout Indonesia. The goal in this article is to know how the political system in the Java community can influence the political system in Indonesia is in the midst of a multicultural Indonesia. The method used to compile this article is the study of literature as well as to observe political and birocration system at this time. The results of this study concluded that directly or indirectly affect the condition of the political system of Indonesia. The political system in the Java community, recognized or not, in fact it has become a standard patern as an overview of Indonesia's current political system. As the dominant tribe, tribal political system currently has more or less successfully Java infiltrated various political systems of other tribes in Indonesia, although in modern bureaucratic agency level, not at the level of the political system of tribal customs is concerned.